(untitled) (IAHS Medical Journal, 2025)
Background: Hypertension is a result of several factors, including unhealthy diet, fast food and avoiding fruits and vegetables. The motive of this study is to evaluate the knowledge and dietary practices regarding prevention and management of HTN. Materials and method: In this cross sectional study, 100 patients were included in the study by purposive sampling. The information were collected from the hypertensive patients coming to private chamber. Results: Out of 100 patients, 67% were males, 57% belonged to age group 40-50 years. 98% of the patients were married, 38% were service holder, 7% were graduates. Among the patients , 42% were aware about HTN, 36% knew normal blood pressure level and 42% had idea about risk factor of HTN. 36% of them believed that HTN is due to family history, 42% due to over weight and 32% due to smoking. To prevent HTN, 85% patients avoided beef consumption, 75% avoided smoking, 95% avoided fatty diet, 42% avoided extra salt intake and 74% adopted regular exercise. Conclusion: This study reflects that the patients had knowledge about HTN and majority had adopted life style modification and self care practice. Educational interventions and awareness development should be focused to improve life style modification among patients. IAHS Medical Journal Vol 7(2), December 2024; 105-108